Direct numerical simulation of two-dimensional stratified gravity current flow with varying stratification and aspect ratio - Lam W.K.; Chan L.; Hasini H.; Ooi A. (Australasian Fluid Mechanics Society, 2023)
Direct numerical simulation; Fluid mechanics; Gravitation; Gravity waves; Numerical models; Reynolds number; Vortex flow; Critical regimes; Gravity currents; Kelvin-Helmholtz; Size and shape; Strong stratification; Subcritical flow; Supercritical flow; Weak stratification; Aspect ratio